2014
DOI: 10.4103/0971-9784.142076
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative localization and monitoring of migrating foreign body using transesophageal echocardiography

Abstract: Radiological imaging is often used for the preoperative localization of foreign body following blast injury, but their utility in case of migration during intra-operative period is limited. Transesophageal echocardiography (TEE) has been used for intra-operative localization and removal of intra-cardiac foreign body; however, reports for localization of extracardiac migrating foreign body are few. Preoperative radiological imaging, in a victim of factory blast-injury, suggested foreign body in the posterior me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The perforation of the esophagus enters in differential diagnosis with LAC especially if there is a positive history of FB ingestion, leading to a major surgery as in our report. The intraoperative transesophageal ultrasound in case of intracardiac sharp FB has been described [8] and could have been of some help in this case.…”
Section: Ingested Foreign Bodymentioning
confidence: 88%
“…The perforation of the esophagus enters in differential diagnosis with LAC especially if there is a positive history of FB ingestion, leading to a major surgery as in our report. The intraoperative transesophageal ultrasound in case of intracardiac sharp FB has been described [8] and could have been of some help in this case.…”
Section: Ingested Foreign Bodymentioning
confidence: 88%
“…Preoperative localization of the foreign body was crucial for its surgical removal. X-rays, CT scans, fluoroscopy, and echocardiography were commonly used to locate the foreign body in the heart 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, most operative suites lack real-time CT or magnetic resonance imaging (MRI). Kumar et al reported a case in which the preoperative radiological imaging showed a foreign body in the posterior mediastinum of a blast-injury victim 7 . However, the foreign body could not be located in the area identified preoperatively during the extended right posterolateral thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…removal can be challenging but necessary due to movement of the heart, proximity to great vessels, and trauma to nearby cardiovascular structures due to potential migration [1][2][3]. Since most foreign bodies are opaque, the initial method of localisation is a chest radiograph [1].…”
Section: Intra-thoracic Foreign Bodymentioning
confidence: 99%